FORMALISATION OF LABOUR: THE ECONOMICS OF PROSTITUTION IN INDIA - Subramanian, Rajeshwari (PEOPLE: International Journal of Social Sciences, 2018)
Prostitution is one of the oldest professions of the world and has been practiced since the birth of the Indian society. The moral ambiguity that engulfs this practice is increasingly bringing out the question of its formalization. This paper assesses the technical shortcomings in India that go unnoticed in the midst of the social debate of a formal industry for prostitution and objectively lays out a steady path for a better socio-economic development. A historical analogy was employed in the prediction of the outcomes of the policy models of the Dutch and Bangladesh in the Indian context by employing economic theories. This application places the questions asked in the context of the current stage of development of India. Along with Growth Indices, Human Trafficking Statistics and trends on HIV/AIDS are superimposed into this because of the direct impact it has on the Prostitution industry and to examine how the legalization affects these statistics. With reference to the analytical insights studied, the paper arrives at a conclusive inference that India is, as yet, not economically equipped to undergo formalization of prostitution. The developing nation does not have the preconditions for ensuring the upward trajectory in the standard of living. This underlines the ever asserted disparity between Growth and Development and the fact that one does not necessitate the other. The findings are backed by statistical data from surveys from national registries, research and reports.